Anxieties of belonging in settler colonialism : Australia, race and place - Slater, Lisa (Routledge studies in cultural history ;, 2019)
"This book analyses the anxiety 'well-intentioned' settler Australian women experience when engaging with Indigenous politics. Drawing upon cultural theory and studies of affect and emotion, Slater argues that settler anxiety is an historical subjectivity which shapes perception and senses of belonging. Why does Indigenous political will continue to provoke and disturb? How does settler anxiety inform public opinion and 'solutions' to Indigenous inequality? In its rigorous interrogation of the dynamics of settler colonialism, emotions and ethical belonging, Anxieties of Belonging has far-reaching implications for understanding Indigenous-settler relations"--